Suspicious minds: user perceptions of privacy on Facebook in Myanmar - Gayani Hurulle; Helani Galpaya; Azamat Ababakirov (International Telecommunications Society (ITS), 2018)
This paper studies the user perceptions of and behaviours pertaining to social privacy on Facebook in Myanmar, drawing on findings of qualitative research from 98 respondents, and an online survey in which 403 responses were received. It explores two elements of the users' behaviour pertaining to social privacy– the means by and the extent to which personal information was shared on the social media platform, and the audiences with whom the information is shared are then examined. The research finds that a number of respondents refrained from publishing their names and photographs on the platform, while individuals with whom they had no offline contact were added to their social network. It finds that the rationales for such decisions had underpinnings pertaining to factors including gender, ethnicity and religion, and were reflective of the socio-political environment in Myanmar at the time of the research.
Keywords: 330